Gender, Microbial Relations, and the Fermentation of Food - Tracy, Megan; Howes-Mischel, Rebecca (Cuizine)

(untitled) (McGill University Library, 2018)
Fermentation is the product of microbial relations that mediate, or foment, relationships between bodies and food products. Using cases of food fermentation made with microbes from ruminants’ stomachs and women’s vaginas, we denaturalize the idea of bodies’ mammalian capacity as linked to particular food relations and explore the traction of gendered ideologies that order exchanges between microbial life to result in such food. This essay first outlines our core argument by situating fermentation within the emergent science on bodily microbial relations, or microbiomes. Incorporating science and technology studies literature together with the feminist literature, we note that the association with lactating, first, aligns one gender more closely with nature and, thus, the other with culture while also leading to the conflation of the feminine with the mammalian. Additionally, this structural alignment with species’ nature ignores that making food from bodies requires culture—both in the sense of culturing microbes and in being reliant on technoscientific processes. We then present two seemingly binary case studies, which are together analyzed through their ability to enroll gender and/or disavow gender in order to produce legitimate food products. We conclude by showing how attention to the ordering and disordering work of microbial relations in the fermentation process both opens up new possibilities for recognizing the way that sex and gender materialize in the capacity of mammalian bodies to ferment and emphasizes that fermentation is always entangled with multiple layers of reproductive labor. Ultimately, such analysis extends food studies scholarship about fermentation into the microbial materiality of gender and food.